L’intégration Des TIC Dans L’enseignement Des Sciences De La Vie Et De La Terre Au Maroc: Etat Des Lieux Et Défis À Relever - Nafidi, Youssef; Alami, Anouar; Zaki, Moncef; El Batri, Bouchta; Hassani, Mohammed Elazami; Afkar, Hanane (European Scientific Journal, ESJ, 2018)
Information and Communication Technologies (ICT) are important educational tools; the measures taken to integrate them into the Moroccan education system are multiple. This study was conducted among 181 teachers of life and earth sciences in a large number of establishments (colleges and high schools). This paper focuses on presenting a diagnosis of the reality of the use of ICT in the teaching of the life sciences and earth in secondary school at the national level; identify teachers’ perceptions of the real benefits offered by the pedagogical integration of these means in education; and determine, according to the conception of the teachers themselves, the main factors that impede or facilitate the effective and efficient integration of ICT in teaching practice. The results of this research show that there is a limited use of ICT, even though most teachers interviewed are convinced of the richness of pedagogical opportunities created by the integration of ICT in education. Thus, ICT generalization projects in the Moroccan education system should take the main constraints highlighted in this research to integrate the digital age into our schools on a more solid foundation.